Bone Mineral Density of Stroke Patients and it's Clinical Relevance - Original Investigation - Nur Kesiktaş; Ayşe Karan; Ayşe Yalıman; Nurten Eskiyurt (Galenos Yayinevi, 2007)
Aim: The aim of this study were to compare paretic and non- paretic side's bone mineral density (BMD) and to investigate whether demographic, clinical and some laboaratory findings were correlated with bone mineral loss or not in stroke patients. Patients and Methods: 46 unilateral stroke patients mean aged 61.8±5.8 were included in the study. Demographic and clinical characteristics of the patients were evaluated. Brunnstrom motor recovery scale, Turkish version of the FIM, Ashworth scale, Beck Depression Inventory (BDI) were used for assessments. Dual-energy X-ray absorptiometry's Biochemical's data were collected. Statistics were analyzed using SPSS version 10.0. Results: The BMDs of the paretic side were statistically significant lower than the non-paretic side at femoral neck BMD/T scores and distal radius T scores (p<0.05). BMDs and T scores of left sided stroke patients were statistically significant lower than non-paretic side at distal radius and femur, but BMD and T scores of right sided stroke patients were not statistically significant different than their non-paretic side BMD of women were statistically significant lower from than men's BMD, (p<0.05) There were a correlation BDI and mobilization, r=-0,379 (p<0.05). Lower functional independence measurements score were found a relationship with osteoporosis. Conclussion: Low FIM scores can predict low BMD. Early walking and mobility must be targeted in stroke rehabilitation. Bigger sample sized, prospective studies must designed for observation of depression effect on osteoporosis in stroke. (From the World of Osteoporosis 2007;13:49-55)